2013
DOI: 10.1111/anu.12044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fishmeal replacement by feather meal in practical diets for juvenile crayfish (Pacifastacus leniusculusDana, Astacidae)

Abstract: The aim of this study was to evaluate different replacement levels of fishmeal (FM) by feather meal (FeM) on survival and growth of juvenile crayfish (Pacifastacus leniusculus). An 80‐day experiment was conducted with stage 2 juveniles from the onset of exogenous feeding. Four practical diets (500 g kg−1 protein) differing in the level of replacement of FM protein by FeM protein were prepared: 0% (control diet), 15% (8.2% dietary FeM), 25% (13.7% dietary FeM) or 35% (19.2% dietary FeM). Each diet was tested on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Non-ruminant processed animal proteins, such as hydrolyzed feather meal (HFM) and poultry by-product meal (PBM) have been used successfully to replace fishmeal protein in the diets of several farmed fish and crustacean species [5][6][7][8][35][36][37][38][39]. However, knowledge of their effects on the histology of digestive organs, the intestinal microbiota and digestive physiology is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…Non-ruminant processed animal proteins, such as hydrolyzed feather meal (HFM) and poultry by-product meal (PBM) have been used successfully to replace fishmeal protein in the diets of several farmed fish and crustacean species [5][6][7][8][35][36][37][38][39]. However, knowledge of their effects on the histology of digestive organs, the intestinal microbiota and digestive physiology is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, when juvenile crayfish were fed a diet in which 15% of fishmeal protein was replaced with hydrolyzed feather meal protein (8.2% feather meal in the diet, unclear the degree of hydrolysis), no significant differences in growth were observed [25]. Munguti et al demonstrated that at least 50% of freshwater shrimp meal in feed can be replaced with hydrolyzed feather meal (unclear the degree of hydrolysis) in semi-intensive culture of Nile tilapia.…”
Section: Growth Performancementioning
confidence: 97%
“…) and feather meal (Fuertes et al . ). Likewise, there are many reports about alternative ingredients in other shrimp species, pea meal (Martinez‐Rocha et al .…”
Section: Introductionmentioning
confidence: 97%